OLS-based asymptotic inference in linear regression models with trending regressors and AR(p)-disturbances - Walter Krämer; Francesc Marmol (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
We show that OLS and GLS are asymptotically equivalent in the linear regression model with AR (p) disturbances and a wide range of trending regressors_ and that OLS based statistical inference is still meaningful after proper adjustment of the test statistics.
Keywords: 519